2015
DOI: 10.1007/s11606-015-3467-3
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Cost and Quality Information in Medicare Advantage Plan Enrollment Decisions: an Observational Study

Abstract: BACKGROUND:To facilitate informed decision-making in the Medicare Advantage marketplace, the Centers for Medicare & Medicaid Services publishes plan information on the Medicare Plan Finder website, including costs, benefits, and star ratings reflecting quality. Little is known about how beneficiaries weigh costs versus quality in enrollment decisions. OBJECTIVE: We aimed to assess associations between publicly reported Medicare Advantage plan attributes (i.e., costs, quality, and benefits) and brand market sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 22 publications
0
28
1
Order By: Relevance
“…Which insurance plans seniors choose has important ramifications for their access to care, out-of-pocket spending, and Medicare costs. In a recent article by Reid et al enrollment decisions in Medicare plans were predicted predominantly by the MA plan's market share (35%), premium and out-of-pocket spending (25% and 12%, respectively), and star ratings (14%; Reid, Deb, Howell, Conway, & Shrank, 2016; Trivedi, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Which insurance plans seniors choose has important ramifications for their access to care, out-of-pocket spending, and Medicare costs. In a recent article by Reid et al enrollment decisions in Medicare plans were predicted predominantly by the MA plan's market share (35%), premium and out-of-pocket spending (25% and 12%, respectively), and star ratings (14%; Reid, Deb, Howell, Conway, & Shrank, 2016; Trivedi, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…One notable study focused on associations between perceptions of care quality and survival for colorectal cancer patients 25 , and found that patients reporting they were "completely satisfied" with their care demonstrated a significantly lower mortality, after controlling for clinical and sociodemographic characteristics. Four focused on quality of the health plan [26][27][28][29] , and all investigated the variability of patient quality ratings across Medicare Advantage (MA) plans and subsequent impact on initial patient enrollment and changes in enrollment. A 2006 study assessed variations in care quality (based on Healthcare Effectiveness Data and Information Set (HEDIS) measures) across racial/ethnic groups, and determined that only 1 plan out of 151 assessed achieved both high quality and low disparity on more than 1 measure 26 .…”
Section: Patient Perceptions Of Care Qualitymentioning
confidence: 99%
“…Xu and colleagues 29 investigated whether MA contract characteristics are associated with quality of care through star ratings and determined that nonprofit (vs. for-profit), larger, and older MA contracts were more likely to receive higher star ratings. An additional study assessed associations between MA plan attributes (cost, quality, and benefits) and beneficiary enrollment, finding that preference for higher quality and lower-cost MA plans with diminishing differences at higher star ratings of 4 and 5 27 .…”
Section: Patient Perceptions Of Care Qualitymentioning
confidence: 99%
“…Surveys have suggested that star ratings play little role in seniors’ plan choices [ 6 , 7 ]. At the same time, quantitative empirical studies have indicated that higher star ratings were in fact associated with higher MAPD enrollment [ 4 , 8 , 9 ]. However, these studies all used cross-sectional study designs and thus could not establish a causal link between ratings and increased enrollment.…”
Section: Introductionmentioning
confidence: 99%